THE EFFECTIVENESS OF USING FIX-UP STRATEGY TO TEACH READING VIEWED FROM STUDENTS’ SELF-CONFIDENCE - Indrasari, Nunun (English Education: Jurnal Tadris Bahasa Inggris, 2015)
NUNUN INDRASARI , 2012. The Effectiveness of Using Fix Up Strategy to Teach Reading Viewed from Students’ Self-confidence (An Experimental Research at the Eighth Grade Students of SMP Negeri 2 Temanggung in the Academic Year of 2011/2012). Thesis. Surakarta. English Education Department of Graduate School, Sebelas Maret University. 2012.The objectives of this study are: (1) to reveal whether Fix-Up Strategy is more effective than Direct Teaching to teach reading; (2) to reveal whether students having high self-confidence have better reading skill than those having low self-confidence; and (3) to reveal whether there is an interaction effect between teaching strategies and the students’ self-confidence on the students’ reading skill.The experimental research was conducted at SMP Negeri 2 Temanggung, from March to April 2012. The sample of the research was two classes; those were VIIID which was treated as experimental class taught by using fix up strategy and VIIIG which was treated as control class taught using by direct teaching. Each of them consisted of 26 students. The data were in the form of quantitative data that were taken from reading test and self-confidence questionaire. The data of reading test were used to know the students’ reading skill. The data of self-confidence questionaire were used to know the students’ level of self-confidence. The data of reading test were the scores of students’ reading test that was administered after having eight times treatment for each class. The researcher analyzed the data using ANOVA or analysis of variance.Based on the result of data analysis, the research findings are: (1) Fix up strategy is more effective than direct teaching to teach reading; (2) the achievement of students’ skill in reading does not depend on the level of the students’ self-confidence; and (3) there is an interaction between teaching strategies and students’ self-confidence. Based on these research findings, it can be concluded that fix up strategy is an effective way to teach reading for the eighth grade students of SMP Negeri 2 Temanggung. From that result, fix up strategy can be implemented at class in order to achieve optimal result. By applying this, the teacher has to facilitate the students to think creatively and actively in reading text by giving fix- up tools, such as previewing, predicting, rereading, monitoring, making connection, visualizing, making inference, and retelling the text.